Cytotoxicity of Bacterial Metabolic Products, including Listeriolysin O, on Leukocyte Targets. (1st October 2012) - Stachowiak, R.; Lyzniak, M.; Budziszewska, B. K.; Roeske, K.; Bielecki, J.; Hoser, G.; Kawiak, J.
Abstract : Bacterial toxins can exhibit anticancer activities. Here we investigated the anticancer effects of the listeriolysin O toxin produced by Listeria monocytogenes . We found that supernatants of Listeria monocytogenes strains (wild type, 1189, and 1190) were cytotoxic to the Jurkat cell line and human peripheral blood mononuclear cells (PBMC) in a concentration-dependent manner. The supernatant of strain 1044, not producing listeriolysin O, was inactive. The supernatants of Listeria strains were also cytotoxic toward B cells of chronic leukemia patients, with no significant differences in activities between strains. We also tested supernatants of Bacillus subtilis strains BR1-90, BR1-S, and BR1-89 producing listeriolysin O. BR1-S and BR1-89 were cytotoxic to PBMC and to Jurkat cells, the latter being more sensitive to the supernatants. BR1-90 was not hemolytic or cytotoxic to PBMC, but was cytotoxic to Jurkat cells in the concentration range of 10–30%, suggesting that listeriolysin O is selectively effective against T cells. Overall, the response of human peripheral blood mononuclear and human leukemia cell lines to bacteria supernatants containing listeriolysin O depended on the bacteria strain, target cell type, and supernatant concentration.